2017
DOI: 10.1002/cncr.30726
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell infiltration and clonality correlate with programmed cell death protein 1 and programmed death‐ligand 1 expression in patients with soft tissue sarcomas

Abstract: BACKGROUNDPatients with metastatic sarcomas have poor outcomes and although the disease may be amenable to immunotherapies, information regarding the immunologic profiles of soft tissue sarcoma (STS) subtypes is limited.METHODSThe authors identified patients with the common STS subtypes: leiomyosarcoma, undifferentiated pleomorphic sarcoma (UPS), synovial sarcoma (SS), well‐differentiated/dedifferentiated liposarcoma, and myxoid/round cell liposarcoma. Gene expression, immunohistochemistry for programmed cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
203
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(223 citation statements)
references
References 46 publications
7
203
1
Order By: Relevance
“…Numerous studies have evaluated the expression of PD‐L1 in DSRCT and synovial sarcoma with conflicting results. While some authors reported high levels of PD‐L1 in DSRCT tissue and in synovial sarcoma, in contrast, and consistent with our findings, two other groups reported very low or no expression of PD‐L1 in either tumor type . We observed extensive heterogeneity of PD‐L1 expression within each tumor type, which might explain the disparate reports.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have evaluated the expression of PD‐L1 in DSRCT and synovial sarcoma with conflicting results. While some authors reported high levels of PD‐L1 in DSRCT tissue and in synovial sarcoma, in contrast, and consistent with our findings, two other groups reported very low or no expression of PD‐L1 in either tumor type . We observed extensive heterogeneity of PD‐L1 expression within each tumor type, which might explain the disparate reports.…”
Section: Discussionsupporting
confidence: 87%
“…In many cases, sarcomas epitomize the most challenging obstacles to overcome in facilitating an immune response. While understanding of the sarcoma immune TME is limited, available data suggest that sarcomas are likely to be cold tumors, with relatively infrequent expression of PD‐L1, low mutational burden, and suppressive immune infiltrates consisting of suppressive macrophages and myeloid derived suppressor cells (MDSCs), rather than exhausted CD8 + T cells . To develop hypotheses for immunotherapy strategies likely to improve responses for resistant sarcomas, we will now examine current and future efforts that aim to build upon immune checkpoint blockade.…”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%
“…As for other tumors types, sarcoma histotypes can be differentiated into "hot-inflamed" or "cold not-inflamed" tumors and these features, as already mentioned, seem to be an approximate predictive biomarker for response to immunotherapies [10,28]. Cold tumors display a completely different immunobiologic signature: lack of type I interferon signature, lack of chemokines for recruitment of T cells, lack of T cells infiltrate, vasculature non-permissive for T cells entry etc.…”
Section: Immune Stimulation To Increase Immune Infiltratementioning
confidence: 99%
“…This heterogeneity is both a challenge and an intriguing model for the study of finetuning mechanisms of the TME. For instance, in a recent paper [10] and their different lymphocytic infiltrate. The authors found a positive correlation between mutational burden, immunogenicity, an abundance of oligoclonal T-cell infiltrates and the great variability of the microenvironmental immune asset among histotypes.…”
Section: Lymphocytic Infiltratementioning
confidence: 99%
See 1 more Smart Citation